A pilot evaluation of using symbol‐based information in police custody. (16th July 2015) - Parsons, Sarah; Sherwood, Gina
Abstract : Accessible summary: Many people who commit crimes in the UK have learning difficulties or disabilities. The police give people information to read in custody, but this information can be confusing. This project presented this information in an easier‐to‐read way using symbols and simple words. We asked different people what they thought of the information and most views were very positive. Summary: At least 20–30% of offenders within the criminal justice system (CJS) have learning disabilities or difficulties. This creates significant challenges in relation to meeting their information needs about rights, entitlements, processes and procedures. We report a pilot project wherewidgit Symbols were used to create more accessible information about rights and entitlements for people entering custody. Thewidgit Symbol custody sheets were used in two Hampshire Constabulary custody centres for a 4‐week period and feedback gathered from 14 custody officers and inspectors. The views of 27 other important stakeholders, including young people with autism and their families, appropriate adults, and senior personnel within the CJS, were gathered about the sheets through interviews and focus groups. The reaction to the sheets was overwhelmingly positive with many participants suggesting that symbol‐based information in custody could be rolled out nationally and also extended more widely to include other parts of the CJS.